THE RELATIONSHIP BETWEEN KNOWLEDGE, PARENTING STYLES, FATHER’S SMOKING HABITS AND STUNTING INCIDENCE AMONG CHILDREN AGED 24–59 MONTHS AT DINOYO COMMUNITY HEALTH CENTER IN MALANG CITY - Zahrotul Fakhriyyah; Farah Paramita; Agung Kurniawan; Nurnanginsih Herya Ulfah (PT. Varians Statistik Kesehatan, 2026)
Background: The latest data from 2024 shows that the stunting rate in Malang City has increased by 5.4%, with the Dinoyo Community Health Center reporting the highest prevalence among the 16 community health centers, at 15.3%. Stunting is a national priority health issue due to its long-term impact on children’s physical and cognitive development. Indirect factors such as parental knowledge, parenting styles, and fathers’ smoking habits also contribute to the occurrence of stunting. This study aims to analyze the relationship between these factors and the incidence of stunting at the Dinoyo Community Health Center in Malang City. Methods: This observational study employed a quantitative cross-sectional design involving 106 respondents selected through purposive sampling. Data were collected via anthropometric measurements and validated, reliable questionnaires, and analyzed using the chi-square test at a significance level of α = 0.05. Results: The results showed significant association between knowledge (P=0.004), parenting style (P=0.004), and the father’s smoking habits (P=0.025) with the prevalence of stunting. Conclusion: that the parenting style variable was the most significant risk factor for stunting, with an Odds Ratio (OR) of 3.9 (95% CI: 1.489–10.719). The conclusion of this study is that sensitive interventions focused on improving parenting practices—particularly regarding feeding practices, sanitation, and psychosocial stimulation—play a crucial role in the growth of infants and toddlers.